Blood glucose response to a calamansi drink in healthy adults: a non‑randomised study - Angela, Siner; Mauna Sree, Sevanesan; Tati, Ambomai; Zakiah, Abd. Wahab; Liwan, Lasem (Springer Nature, 2020)
Objective: Glycaemic Index (GI) ranks the body’s response to carbohydrate content in food such that high GI food increases postprandial blood glucose levels. One of the popular drinks at food and beverage outlets is a drink made from calamansi, a citrus that is believed not to induce an increase in blood glucose levels. In this non-randomised single-blind (participants) study, capillary blood from 10 healthy males were sampled following consumption of either glucose or the calamansi drink. The blood glucose measurements were then used to calculate the GI for the drink. Results: The GI of the calamansi drink tested was calculated as 37, a value within the range of low GI foods. Trial registration Clinical Trials identifier NCT04462016; Retrospectively registered on July 1, 2020.